A Review OF THE Prospects and CHALLENGES in Marketing THE Homoeopathy medicineS - P. K , SUDHIR.; SHIVASARAVANAN, A. S. (International Journal of Psychosocial Rehabilitation, 2020)
The Term Homoeopathy is derived from the Greek words ‘hómoios’ means similar and ‘pathos’ means suffering, the disease. Homoeopathy has a holistic approach to healing, with as its central theme that “like cures like” in Latin it is similia similibus curentur. In India, where Homoeopathy is a National Medical System, the market is growing at 25 percent a year, and more than 100 million people depend solely on this form of therapy for their health care. The unhealthy lifestyle of urban people and daily consumable products which are polluted with dangerous chemical substances, affects their overall health. These exclusive effects of these practices can be spread out more in urban population by conducting workshops, seminars, discussions, actively coordinating research projects, Homoeopathic counseling programs, radio talk shows and Television programs. This review tries to get inside into the various marketing initiatives and helps to understand issues and challenges in marketing of homoeopathy. The findings indicate that implementing new marketing initiatives of Homoeopathy by identifying the major issues and challenges may turn out to be more marketable. Various recommendations are given on the basis of the findings which indicate how different marketing initiatives of Homoeopathy can fight with other Alternative medical systems in Indian urban market. This review has implications for Homoeopathic practitioners in India, academicians, marketing people, researchers and interested people of this medical system.